Factors Affecting Nurses in Implementing Patient Safety in Hospitals: A Literature Review - Adinda Nur Salsabila; Inge Dhamanti (Universitas Nahdlatul Ulama Surabaya, 2023)
Patient safety is the most important indicator in the healthcare system that is expected to be a reference for producing ideal healthcare services and reducing patient incidents. The nurse factors are the main factor related to patient safety because nurses interact more often with patients. This study aims to identify the factors influencing nurses implementing patient safety in hospitals. This article was a literature review with a descriptive approach by collecting several journals and articles from the Indonesia One Search and Google Scholar databases with specified inclusion criteria. Based on the results of a review of six articles shows that several factors influence nurses in implementing patient safety, including age, attitude, knowledge, work motivation, workload, length of work, supervision, and organizational culture. The implementation of patient safety goals by nurses in hospitals can be categorized as either good or bad because several factors influence it. For this reason, the coordination of the hospital must carry out activities to strengthen the factors that affect nurses so that patient safety can be adequately implemented.